12 Weeks of a Ribavirin‐Free Sofosbuvir and Nonstructural Protein 5A Inhibitor Regimen Is Enough to Treat Recurrence of Hepatitis C After Liver Transplantation. Issue 4 (5th October 2018) - Houssel‐Debry, Pauline; Coilly, Audrey; Fougerou‐Leurent, Claire; Jezequel, Caroline; Duvoux, Christophe; De Ledinghen, Victor; Radenne, Sylvie; Kamar, Nassim; Leroy, Vincent; Martino, Vincent Di; D'Alteroche, Louis; Canva, Valérie; et al.
Abstract : Sofosbuvir (SOF) combined with nonstructural protein 5A (NS5A) inhibitors has demonstrated its efficacy in treating a recurrence of hepatitis C virus (HCV) after liver transplantation (LT). However, the duration of treatment and need for ribavirin (RBV) remain unclear in this population. Our aim was to determine whether LT recipients could be treated with an SOF + NS5A inhibitor‐based regimen without RBV for 12 weeks post‐LT. Between October 2013 and December 2015, 699 LT recipients experiencing an HCV recurrence were enrolled in the multicenter ANRS CO23 CUPILT cohort. We selected patients receiving SOF and NS5A inhibitor ± RBV and followed for at least 12 weeks after treatment discontinuation. The primary efficacy endpoint was a sustained virological response 12 weeks after the end of treatment (SVR12). Among these 699 patients, 512 fulfilled the inclusion criteria. Their main characteristics were: 70.1% genotype 1, 18.2% genotype 3, 21.1% cirrhosis, and 34.4% previously treated patients. We identified four groups of patients according to their treatment and duration: SOF + NS5A without RBV for 12 (156 patients) or 24 (239 patients) weeks; SOF + NS5A + RBV for 12 (47 patients) or 24 (70 patients) weeks. SVR12 values reached 94.9%, 97.9%, 95.7%, and 92.9%, respectively ( P = 0.14). Only 20 patients experienced a treatment failure. Under multivariate analysis, factors such as fibrosis stage, previous treatment, HCV genotype, and baseline HCV viral load did not influence SVR12 rates in the four groups ( P = 0.21). Hematological adverse events (AEs) were more common in the RBV group: anemia ( P < 0.0001) and blood transfusion ( P = 0.0001). Conclusion: SOF + NS5A inhibitors without RBV for 12 weeks constituted reliable therapy for recurrent HCV post‐LT with an excellent SVR12 whatever the fibrosis stage, HCV genotype, and previous HCV treatment. (Hepatology 2018; 00:000‐000).